Sustainable Dam Development: Balancing Hydropower, Water Management, and Environmental Conservation in a Changing Climate - Ilmi, Abu Dedo (Journal of Sustainable Infrastructure, 2025)
The development of dams plays a pivotal role in global water management, hydropower generation, and environmental conservation. However, as climate change accelerates, the traditional approaches to dam construction and operation are being challenged. This review examines the need for a sustainable approach to dam development, focusing on the balance between hydropower production, efficient water management, and environmental conservation. It explores the current challenges posed by climate change, including altered hydrological cycles, the impact on ecosystems, and the shifting energy demands. Additionally, the review highlights innovative approaches, including the integration of green technologies, environmental monitoring, and adaptive management strategies. The aim is to provide insights into how dams can be developed and operated in a way that supports sustainable development goals, particularly in the face of climate uncertainties